Gelation and microstructural properties of a millet‐based yogurt‐like product using polymerized whey protein and xanthan gum as thickening agents. Issue 11 (26th October 2020) - Song, Xiao; Sun, Xiaomeng; Ban, Qingfeng; Cheng, Jianjun; Zhang, Siyu; Guo, Mingruo
Abstract : Abstract: Cereal‐based fermented products are becoming popular in the world. A millet‐based yogurt‐like product (MYP) using polymerized whey protein (PWP) and xanthan gum (XG) as thickeners was developed. The present study aimed to investigate the effects of PWP (0.3 to 0.5%, w/v) and XG (0 to 0.2%, w/v) on the gelation properties and microstructure of MYP. All samples were analyzed for rheological properties, textural properties, microstructure, and pH value during fermentation. The MYP Ⅲ (0.4% PWP and 0.1% XG) registered the highest elastic modulus ( G′ ) throughout the fermentation and cooling steps ( P < 0.05), but MYP Ⅳ (0.35% PWP and 0.15% XG) had the highest apparent viscosity compared with the other samples. No significant differences in the pH values among the samples were observed during the fermentation process ( P > 0.05). The hardness value of MYP Ⅳ reached a maximum after 4 hr and then stabilized during fermentation. Scanning electron microscopy showed a compact and uniform network for the MYP with PWP and XG. MYP Ⅳ had the best texture properties (hardness, springiness, and gumminess). Overall, PWP (0.35%, w/v) and XG (0.15%, w/v) were the best combination for MYP as a thickening system. Practical Application: Cereal‐based fermented products have attracted much attention in the food industry. However, due to absence of a natural protein network, it is hard to produce a set‐type millet‐based yogurt with a firm texture under the studied conditions without adding any thickening agents. In this study, PWP (0.35%, w/v) and XG (0.15%, w/v) can be used for fermentation of millet‐based yogurt‐like products. The new cereal‐based fermented product would be a promising food in the market.